If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -48 + -8x = 31 + -15x Solving -48 + -8x = 31 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. -48 + -8x + 15x = 31 + -15x + 15x Combine like terms: -8x + 15x = 7x -48 + 7x = 31 + -15x + 15x Combine like terms: -15x + 15x = 0 -48 + 7x = 31 + 0 -48 + 7x = 31 Add '48' to each side of the equation. -48 + 48 + 7x = 31 + 48 Combine like terms: -48 + 48 = 0 0 + 7x = 31 + 48 7x = 31 + 48 Combine like terms: 31 + 48 = 79 7x = 79 Divide each side by '7'. x = 11.28571429 Simplifying x = 11.28571429
| (x+5)-2(3-4x)=4(x+5)-1 | | -4=-6n-(6n-2) | | 8x+-8=x+7 | | 4(x+2)+6x=20 | | 2x-1overx=-1 | | -6/5*30 | | -50y=3y-8 | | 2c^3-4c^2-70c=0 | | 2(x-2)+x+x+3=25 | | 5n-16=8n-10 | | 2*ln(x+1)=ln(2x) | | 2x^2+28x+103=30 | | 15x-20=8x+16+5 | | 2+-3/4=6 | | [s+3(s-1)]=18 | | 5/7/35 | | 10-1/2x=6x-3 | | 18+c/4=32 | | 18+c/4=32 | | -6.8-(-6.4)= | | (X+2)-2(2-2x)=2(x+4)-1 | | 28000n+3000n=36000n+2000n | | -3*(h-6)=5*(2h+3) | | 6(x+5)*4=3x-5 | | 0.5x+0.5=x+1 | | 4+-45= | | 16/4/5 | | 7+6x=4x-13 | | -3x^2-7x+5= | | 40+x=60 | | 15-4z=10 | | 13-19.2= |